How Does ARBook Promotional Media For MSME Crafts Using Augmented Reality Marker Tracking Works? - Hermawan, Hardika Dwi; Noor, Zakky Muhammad; Ulfatun, Titik; Nonalisa, Septiarida; Saputri, Agatha; Yuliana, Irma (Bina Bangsa International Journal of Business and Management, 2021)
The present study aimed to develop a virtual book displaying Jogja craftwork using Augmented Reality (AR) technology as an interactive promotional media to advertise handicraft products originated from the Special Region of Yogyakarta. "Buku Kerajinan Jogja" (Jogja Handicraft Book) application under this research was developed through Research and Development (R&D). The first stage of its Development was needs analysis and literature study, followed by designing the application using Use Case driven object modeling. The next was the development stage of the application and its functional testing by two media experts. In the fourth stage, two-steps software testing was carried out, namely (1) verification and validation test, and (2) quality and feasibility testing to examine its functionality, usability, portability,  efficiency,  maintainability,  and reliability  (ISO  9126-1).  The findings suggest that (1) the Development of the product, Buku Kerajinan Jogja,  might have gone through a  series of proper software engineering processes from design to testing consistent with the desired specifications. Secondly, (2) the overall performance of Buku Kerajinan Jogja seems to be "Good" with test results of 82.98%, 82.5%, 83.3%, 85.0%, 75.0%, 75.0% consecutively for usability, functionality, reliability, portability, maintainability, and efficiency (ISO 9126-1)